The growing burden of multidrug‐resistant infections among returned Australian travellers. Issue 2 (3rd February 2014) - Chua, Kyra Y L; Grayson, M Lindsay; Burgess, Adele N; Lee, Jean Y H; Howden, Benjamin P
Clinical record: A previously well 66‐year‐old man was repatriated from Athens, Greece, to the Austin Hospital for ongoing management after a protracted hospital admission for an ischiorectal abscess secondary to perforated diverticulitis. This was complicated by faeculent peritonitis, multiple intra‐abdominal abscesses and necrotising fasciitis of the abdominal wall. These complex problems required multiple laparotomies to drain and debride the abscesses, management of an open abdomen with vacuum‐assisted closure dressings, and the formation of a loop sigmoidostomy. He also developed a grade IV sacral pressure ulcer with underlying sacral osteomyelitis. Organisms isolated from the intra‐abdominal collections included carbapenem‐resistant Pseudomonas aeruginosa and a carbapenemase‐producing Klebsiella pneumoniae ( bla KPC ). Due to the complexity of the patient's illness, he had spent 93 days in hospital in Greece, predominantly in intensive care, with three interhospital transfers within Greece before repatriation to Australia. Antibiotics administered in Greece included tigecycline, colistin, fosfomycin, vancomycin, clindamycin and anidulafungin. As the patient had multiple resistant organisms, detailed infection control plans were made before his arrival at the Austin Hospital. This included placement in a single room with a dedicated ensuite bathroom, daily bleach cleaning of the room, 1 no use of shared equipment, enforcement of strict contact precautions including gowns and gloves, and hand hygiene. Patient movement was severely restricted and only two visitors were allowed at any one time. Unfortunately, the patient developed a new intra‐abdominal collection, bowel obstruction and abdominal sepsis. This required surgical intervention, including extensive division of adhesions, resection of the sigmoid and part of the descending colon, retroperitoneal enteric fistula repair and retroperitoneal abscess drainage. An end colostomy and loop ileostomy were formed. This procedure resulted in faecal continence and therefore control of the perianal source of multidrug‐resistant organisms. Culture of the intra‐abdominal abscess grew mixed enteric flora including Enterococcus faecium, Escherichia coli, Citrobacter spp, Candida glabrata and K. pneumoniae . The latter organism was resistant to multiple drugs, including meropenem, due to the production of K. pneumoniae carbapenemase‐2 ( bla KPC‐2 ) (Patient 1, Box). The same organism was found in his faeces. A bla KPC‐2 ‐producing K. pneumoniae was also isolated from a sacral ulcer swab, but the susceptibility profile was slightly different. This isolate was also resistant to all aminoglycosides, including gentamicin and amikacin, and demonstrated an increased minimum inhibitory concentration to colistin (Box). The patient's antibiotic treatment included meropenem, tigecycline, colistin and caspofungin for 6 weeks, and his sacral ulcer was treated with a vacuum‐assisted closure dressing. He stayed at the Austin Hospital for 101 days before being discharged home. Six months later, the patient re‐presented to the Austin Hospital with urosepsis. The causative organism, isolated in both urine and blood, was E. coli (Box). Strikingly, the organism was found to be a bla KPC‐2 ‐producing strain, suggesting interspecies transfer of this mobile genetic element between K. pneumoniae and E. coli . Unlike the K. pneumoniae, this isolate was susceptible to ciprofloxacin, and the patient was successfully treated with this antibiotic. During this second admission, the same infection control measures were enforced. At follow‐up 6 months later, the patient remained well. There was no documented inhospital transmission of bla KPC‐2, suggesting the infection control measures employed were successful.